SISTEM PENDETEKSI SUHU DENGAN SENSOR MLX00614 BERBASIS NODE MCU ESP8266 - sunaryono sunaryono (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2023)
Body temperature is one of the vital signs which has meaning as an indication of the activities of the organs in the body. Examination of vital signs is a way to detect changes in body systems. Assessment/examination of vital signs is used to monitor the patient's development and to find out any abnormalities in the body is used as a support in helping to determine the diagnosis. Temperature measurement is not just a routine but an action to monitor changes/disorders of the body system. To find out body temperature, a temperature measuring device is needed, one of which is a thermometer. In the design we have to collect data and identify hardware requirements to build a Prototype Human Body Temperature Detection Tool Sound Notification Using a Microcontroller, NodeMCU esp8266 is needed as a microcontroller programmed with Arduino IDE, USB cable to connect the tool with a laptop, Jumper Cables to connect between components, Laptop/ PC for coding, Ultrasonic sensor for motion detection, DF Mini player for storing mp3 sound files, MLX00614 sensor for temperature detection, 16x2 LCD for temperature display, Speaker for sound output Prototype of the Human Body Temperature Detection Device Sound Notification Using a Microcontroller has been successfully implemented, namely the Ultrasonic Sensor has successfully detected motion and the MLX00614 Sensor has successfully detected temperature which then sends data to NodeMCU eps 8266 which is then processed to give commands to DF Mini player to issue a temperature sound generated via speaker. NodeMCU eps 8266 also sends temperature data to the 16x2 LCD for display. Implementation success can be seen from the product test scores obtained by 90% ≥ 75%, the product is declared successful and the benefits test results are Useability 96%, Learnability 96%, Efficiency 95% and Acceptability 95%.